German Energy and Decarbonization Scenarios: “Blind Spots” With Respect to Biomass-Based Carbon Removal Options - Hahn, Alena; Szarka, Nora; Thrän, Daniela (Frontiers in Energy Research, 2020)
In 2019, the German government agreed on a Climate Protection Program intended to deliver its 2030 climate targets. Concrete measures, such as a carbon price, will be put in place as early as 2021. But how to plan beyond 2030? Scenarios can be powerful tools to envision the world in 20, 30, or 50 years, to describe pathways toward different visions of the future, and ultimately to investigate technology portfolios and policy options against their performance toward the achievement of a decarbonized future. This is why scenarios are especially popular with energy and climate scholars. In particular, scenarios with biomass-based carbon removal options (BCO2) can help to highlight how we may reach a net negative emission world. Hence, in this study, 66 energy and decarbonization scenario studies are systematically reviewed for Germany from the years 2002 to 2019 to assess how inclusive they are with regard to BCO2 concepts. The portfolio of BCO2 concepts within those scenarios is studied over time and a qualitative analysis of the scenario documentation is performed to identify the rationales for their inclusion or exclusion. The results indicate “blind spots” of the scenarios with regard to bioeconomy aspects, as biomass for material use is only sparsely covered. Likewise, only about 10% of the studies provide a framework for land use changes and corresponding emission accounting to adequately represent biomass-based negative emission technologies (NETs) in their assessments. The analysis for carbon capture and storage (CCS) further reveals the necessity of revisiting the public acceptance argument which has previously served so far for many studies as the ultimate, though not well-grounded deal-breaker. Based on the detected gaps and shortcomings in the current German scenario landscape, recommendations for a more transparent and holistic representation of BCO2 in the scenario framework are given.